Effects of Vitamin D Supplementation on Blood Pressure in Patients With Type 1 Diabetes Mellitus: A Systematic Review of Clinical Trials - Rasoul Ebrahimi; Mohammad Mahdi Masouri; Amir Abbas Salehi Amniyeh Khozani; Sana Mohammad Soltani; Seyed Aria Nejadghaderi (Health Science Reports)
ABSTRACT Background and Aims Hypertension exacerbates cardiovascular risks in patients with type 1 diabetes mellitus (T1DM), necessitating effective blood pressure (BP) management. Vitamin D deficiency is common in T1DM patients and is associated with an increased risk of cardiovascular diseases. This systematic review aimed to evaluate the impact of vitamin D supplementation on BP in T1DM patients. Methods PubMed, Web of Science, Embase, Scopus, and Google Scholar were searched until March 2024. Clinical trials reported BP outcomes in patients with T1DM after vitamin D supplementation were included. Other types of studies and studies that did not report BP outcomes and those that had populations other than patients with T1DM were excluded. The National Institutes of Health (NIH) tool was used for the risk of bias assessment. Results In total, eight studies, involving 328 participants, were included in this review. They were conducted between 2014 and 2024, with mostly conducted in Brazil (n = 5). While one study demonstrated a significant reduction in morning systolic and diastolic BP after vitamin D supplementation, five studies found no significant differences in systolic or diastolic BP. Another study noted a significant reduction in morning systolic and diastolic BP, with no significant changes in 24‐h ambulatory monitoring. Also, paricalcitol therapy did not significantly reduce systolic and diastolic ambulatory BP compared to placebo. Conclusion The current evidence on the effect of vitamin D supplementation on blood pressure in patients with T1DM remains inconclusive. Nonetheless, more randomized controlled studies with larger sample sizes and longer follow‐up durations are essential to establish the association between vitamin D and BP in this population.